Factors Related to Breastfeeding Self Efficacy of Exclusive ASI in the Mawar Room RSI Jemursari Surabaya - Rahmadaniar Aditya Putri; Lia Indriani; Siti Nur Hasina; Syiddatul Budury; Wesiana Heris Santy (Journal Of Nursing Practice, 2025)
Background: The lack of a mother's self-confidence and confidence in breastfeeding is the single biggest factor causing failure in recruiting exclusive breastfeeding. Mothers' belief in the success of exclusive breastfeeding is known as the effectiveness of breastfeeding. Purpose: The purpose of this study was to examine various variables related to the self- efficacy of exclusive breastfeeding in the Mawar room of RSI Jemursari Surabaya. Methods: This type of analysis is a cross-sectional analysis. The population of each mother is at least 120 people. Purposive sampling is used in the selection of non-probability samples with a total of 92 respondents. Observation of other people, verbal persuasion, physical and emotional condition, and breastfeeding self-efficacy are examples of independent behavioral variables. Using a questionnaire as an instrument breastfeeding scale short form questionnaire. Data analysis used the Chi-Square test and Spearman's Rank with a significance level of p=0.05. Results: The results showed that most of the respondents with good observation factors for others had a high level of breastfeeding self-efficacy (67.7%), almost all respondents with good verbal persuasion factors had a high level of breastfeeding self-efficacy (78.8 %), and most of the respondents who were in good physical and emotional condition had a high level of breastfeeding self-efficacy (62%). The results of the Chi-Square test showed that there was a relationship between the observation of other people with a result of p = 0.000 <0.05 and physical and emotional condition factors with a result of p = 0.000 <0.05 with breastfeeding self-efficacy. Spearman's rank test showed that there was a relationship between the verbal persuasion factor and the results of p = 0.000 <0.05 with breastfeeding self-efficacy for exclusive breastfeeding in the Mawar room of RSI Jemursari Surabaya. Conclusion: Observation of other people, verbal persuasion, physical condition, and emotional state are interrelated factors. Therefore, it is hoped that there will be more formal and informal education about exclusive breastfeeding, especially for new parents.